PEMBANGUNAN FISIK SEBUAH KOTA : Menipisnya Public Space? - Kusumo, Ririn Sumari (Universitas Katolik Soegijapranata, 2012)
Semarang as a capital city gives a good impression to other cities. Semarang has established infrastructure for city population for years. The establishment of infrastructure. unfortunately. takes public spaces and affects public space availability. Prior, Simpanglima Park was a public space which changed its function to be the area of food /consumer goods paddlers. So there lWlS no space available for entertainment activities of the population. There mzs not only Simpanglima. but also Taman KB that its condition was screaming. Visitor who came to the park felt unsatisfactory caused by impolite and crime baggers. There were so food paddlers who sell food with un-normal prices as well as garbage and its bad smelt problems. At the end. people prefer malls for passing the time or entertainment. Only with 1000 to 2000 rupiahs for park retribution they can avoid impolite sellers, crime baggers and got cool air atmosphere. But nowadays. the Government has been improving the lnfrastructure so the public spaces have been returned to their function